Biological aspects of the two-spotted spider mite on strawberry plants under silicon application - Ribeiro, Edenilson B.; Castellani, Maria Aparecida; Júnior De Andrade, Daniel [UNESP]; Prado, Renato De M. [UNESP]; Souza, Larissa Adelita S. C.; Freire, Daniel S.; Savi, Patrice Jacob [UNESP] (FapUNIFESP (SciELO), 2021)
Silicon is an inducer of plant resistance to arthropod pests, being a promising strategy for integrated management. The aim of this study was to evaluate the effect of silicon on biological, reproductive and population aspects of parental and F1 generations of the two-spotted spider mite on strawberry plants. Potassium silicate, nanosilica and water were applied to the plants. Two-spotted spider mite females were confined to strawberry leaf disks for oviposition and, after hatching, larvae were observed until the emergence of adults. Once adults had been obtained, couples were formed in order to evaluate pre-oviposition, oviposition, longevity and fertility, with an estimated net reproduction rate, intrinsic rate of increase, finite rate of increase and the necessary time for doubling the generation. Silicon prolonged the duration of some immature stages of the mites in parental and F1 generations, did not affect the duration of the whole biological cycle, though. The periods of pre-oviposition, oviposition and longevity of the parental generation and the longevity and oviposition of F1 generation of the two-spotted spider mite were negatively affected by potassium silicate and nanosilica. The population parameters of the parental generation of the mites indicated that nanosilica is able to lead to a long-run decrease of this pest population.
Aspectos biológicos do ácaro-rajado em morangueiro sob aplicação de silício
Keywords: Induced resistance; Nanosilica; Potassium silicate; Tetranychus urticae